Thermal, morphological and surface properties of composite materials with perlite reinforcement - Bilgiç Ceyda; Karakehya Naile; Voelkel Adam (Journal of the Serbian Chemical Society)
This paper deals with the preparation and the characterization of perlite/polyvinyl alcohol, perlite/polyvinylpyrrolidone, perlite/polymethyl methacrylate and perlite/polystyrene composites. The polymer composites were prepared by solvent casting technique with 5 wt. % of perlite filler. Perlite is a filler with unique properties, such as low density and thermal conductivity, thus the development of Polymer–Perlite composites may be of interest for producing lighter packaging with thermal insulation capability. The perlite/ /polymer nanocomposites were characterized using X-ray diffraction (XRD) analysis, thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), inverse gas chromatography (IGC), field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). TGA measurements showed remarkable increases in the thermal stability of the polystyrene by the perlite loading as compared to the matrix. The FE-SEM image of the cryomilled sample shows that the perlite particles were embedded within a polystyrene matrix. This finding is consistent with the work of adhesion data obtained by IGC.